From Language Anxiety to Professional Excellence Among Indonesian Employees - Alpino Susanto; Sri Langgeng Ratnasari; Albert Efendi Pohan; Tubagus Pamungkas; Linayati Lestari; Joy Early Wahyuni Simarmata (Vision: Journal for Language and Foreign Language Learning, 2025)
Although the demand for English proficiency in the workplace is increasing, limited research has examined its effects on employees' self-efficacy and job performance. English skills are essential for communication, productivity, and career advancement, yet their Influence on workplace outcomes remains understudied. This study investigates the relationship between employees' English self-efficacy and their professional performance using a mixed-methods design. A closed-ended survey was administered to 32 employees across five companies, and additional qualitative insights were collected from three managerial leaders. Quantitative data were analyzed through statistical correlation, while qualitative data were examined using thematic analysis. Findings show a strong correlation (r = .57) between English self-efficacy and job performance, indicating that employees who feel confident in their English abilities tend to perform more effectively. Managers also emphasized that English proficiency is especially important for supervisory and managerial roles. The study concludes that higher English self-efficacy positively contributes to job performance. However, its scope is limited by a small sample drawn from an electronics manufacturing company and by feedback from only three managerial interviewees, reducing the generalizability of the findings. Future research should explore a broader range of international workplace contexts to better understand how learning communities and vocational training can strengthen employees' language skills and performance.